Improved anti-nociceptive, anti-pyretic and anti-inflammatory effects of orally administered liposome-encapsulated piroxicam - Chiong, H.S.; Yong, Y.K.; Mohd Hijaz, M.S.; Sulaiman, M.R.; Yuen, K.H.; Hakim, M.N. (Oriental Scientific Publishing Company, 2024)
Piroxicam, a nonsteroidal anti-inflammatory drug, has been shown with low oral bioavailability and delayed onset of its therapeutic effects. In this work, a promising nano/ liposomal drug delivery system was exploited to improve the in vivo therapeutic efficacies of piroxicam. The current liposome-encapsulated piroxicam formulation effectively boosted and prolonged peripherally mediated anti-nociceptive activities in tests for abdominal writhing induced by acetic acid (inhibition of pain 70.19% was in mice treated with 30 mg/kg liposome-encapsulated piroxicam), paw licking induced by formalin (81.36% inhibition when compared to free unencapsulated piroxicam), and hyperalgesia induced by carrageenan (55.8% inhibition when compared to free unencapsulated piroxicam). Even lower dose of liposomes-encapsulated piroxicam was also significantly inhibit Brewer’s yeast-induced hyperthermia. Carrageenan-induced paw-edema test and cotton pellet-induced granuloma test revealed that liposomes-encapsulated piroxicam had significantly more potent acute and chronic anti-inflammatory effects than piroxicam, even if lower drug dosages were used to treat animals. A better modulation in the generation of inflammatory mediators (nitric oxide, tumour necrosis factor-a, interleukin-1ß, and interleukin-10) at 18.02% (TNFa), 23.97% (IL-1ß) and 10.27% (IL-10) inhibition when compared to 30mg/kg free piroxicam group respectively. was ascribed to the higher in vivo therapeutic actions. Present nano-encapsulated piroxicam also significantly enhanced the inhibition of cyclooxgenase-2 (total percentage inhibition was increased by 18.25% and 19.22% at drug dosage of 3 and 30 mg/kg, respectively), but not cyclooxgenase-1 enzyme. In conclusion, present study showed that liposomal drug formulation was able to improve the in vivo therapeutic effects of orally administered piroxicam.